Respuesta :
[tex]\dfrac{2x -3}{5} - \dfrac x3 \leq 2\\\\\implies \dfrac{6x-9-5x}{15} \leq 2\\\\\implies x-9 \leq 15 \times 2\\\\\implies x -9 \leq 30\\\\\implies x \leq 30 +9 \\\\\implies x \leq 39\\\\\text{Interval,}~ (-\infty, 39 ][/tex]
Answer:
x
Step-by-step explanation:
Refer to '<' as ' less than or equal to '
Whenever you are deal with these types of inequalities / equations, nake sure to equate the denominators of both entities involved in the operation be it ( -, × , ÷ ,+ )
with that in mind
* 2x - 3/5 - x/3 < 2 has 2 different denominators i.e - 5 & 3
so to equate both sides, let's multiply each by the denominator they are lacking.
* 2x - 3/5 lacks 3 compared to -x/3.
* similarly, -x/3 lacks 5 compared to 2x - 3/5
multiply both by what they lack (2)
thus, (2x - 3 )×3 /(5) × 3 - (x × 5) × 5/ (3) × 5 < 2
* 6x - 9/ 15 - 5x/15 < 2
we can now combine the numerators since we now have a common denominator which is 15.
* 6x - 9 - 5x/ 15 < 2 (6x-9-5x) is equal to -9 + x = x - 9.
criss cross
* x - 9 < 30
* x < 39